Semidirect posterior composite restorations with a flexible die technique A case series - Gomes Torres, Carlos Rocha [UNESP]; Zanatta, Rayssa Ferreira [UNESP]; Rocha Lima Huhtala, Maria Filomena [UNESP]; Borges, Alessandra Buhler [UNESP] (Amer Dental Assoc, 2017)
Background and Overview. Besides indirect use in the laboratory and direct use for restorations, composites can be used in semidirect procedures. The authors describe the semidirect composite restoration technique by using a flexible die for large lesions in posterior teeth. Case Description. The authors present illustrations of the clinical steps and the outcomes immediately after the procedures. The authors placed chairside inlay, onlay, and overlay composite restorations. The final esthetic outcome, along with function and anatomic form recovery, demonstrated that this might be a viable cost-effective alternative technique to laboratory-fabricated indirect restorations. Conclusions and Practical Implications. Clinicians can restore large preparations in posterior teeth successfully with semidirect composite restorations in a single appointment by using the flexible die technique, resulting in satisfactory function and esthetic outcome.
Keywords: Composite resins; semidirect restoration; dental esthetics; shrinkage